PENGARUH HARGA BERAS TERHADAP HARGA GABAH DI TINGKAT PETANI - Yogi, .; Lihan, Irham (Lampung University)
This research intends to determine the impact of fluctuation of rice price on the farm gate price. The study is employing survey method and data partially was obtained from Department of Agriculture website. Data analysis was using power function of multiple regression analysis. The study suggests that there is strong influence of price fluctuation at consumer to the farm gate price. However, the fluctuation between the two was not proportional where as farm gate price is less fluctuated than the consumer price. The study also suggests that only if the price at consumer increase by 100%, farm gate price will increase by 33% only the remaining 67% are enjoyed by retailers. This reflects that marketing system at farm level is less competitive.